Features Of Hellenism In The Spiritual Culture Of Ancient Armenia - Sargsyan, G. Kh. (ՀՀ ԳԱԱ)
Gagik Sargsyan was a prominent Armenologist and expert in ancient Near Eastern civilizations. His scientific interests included several key problems of Armenian history - social-political history of ancient Armenia, Hellenism in Armenia, historicity and chronology and of Movses Khorenatsi’s "Armenian history", Pre-Mesropian Armenian historiography, the problem of Urartu-Armenia and issues of the formation of the Armenian people etc. Below the editorial board presents full text of his report at the international conference “Eirene” (1976) which deals with the problem of the impact of Hellenism on the spiritual culture of ancient Armenia.
Keywords: Armenological Heritage